Analisis Penentuan Desa Pusat Pertumbuhan Di Kecamatan Lembar Kabupaten Lombok Barat - Salmah, Emi; Sahri, M; Astuti, Endang (Jurnal Ekonomi dan Bisnis, 2018)
This study aims to: a). Identify the availability of facilities and infrastructure for each village in Sheet District, b). Determine suitable villages to be developed as the Growth Center Village in Lembar District. The type of research used is descriptive research. The results of the study show that the facilities and infrastructure in Lembar District in general are sufficiently available and have supported the establishment of the Center for Growth Village. The appropriate village to be developed as a Growth Center Village is Kembar Bridge Village because the weight obtained from 7 (seven) DPP determinant variables is 73, which means Twin Bridge Village. have facilities and infrastructure and have the potential to support the formation of the Growth Center Village in Lembar District, West Lombok Regency. Referring to the results of the analysis and discussion in the previous chapter and referring to the results of the above research, suggestions can be made, namely the need to develop several facilities and infrastructure to further improve the function of Twin Bridge Village as a growth center for the hinterland areas such as communication facilities, education, and procurement of business entities or companies.